Wideband hybrid metamaterial absorber via compound design of multiple mechanisms - Wang, Zhenxu; Xiong, Xinmeng; Liang, Jian-Gang; Wang, Jiafu; Fu, Xinmin; Ding, Chang; Han, Yajuan; Sun, Yong; Wang, Yudeng; Zhou, Junxiang; Jiang, Juanna; Wang, Wenjie; et al. (Frontiers in Physics, 2023)
Broadband and high efficiency are the two core indexes of absorption research, which usually requires a balance between them. Therefore, how to take into account both and achieve broadband and efficient absorption is a hot topic in current research. In this paper, by the compound design of multiple mechanisms, a kind of wideband hybrid metamaterial absorber (HMA) is proposed. The overall structure consists of a layer of patterned resistive film and a layer of magnetic absorbing material (MAM) separated by the air. The resistive layer is designed as square ring type to regulate the local magnetic field, which results in significant magnetic field enhancement within the MAM layer, and this mechanism provides a prerequisite for wideband and high-efficiency absorption in the low frequency band. Furthermore, due to the electrical losses of the resistive film, another absorption band is additionally excited in the high frequency band. Thanks to the multiple mechanisms, the absorption efficiency above 90% in the 3.2–22.0 GHz frequency band can be realized, and the thickness of the overall structure is 7.0 mm that is 0.07 of the wavelengths at the lowest frequency point. To demonstrate this method, a prototype is designed, fabricated and measured. Both the simulation and experiment results verify the effectiveness of the proposed method. This work provides a new method to design wideband and high-efficiency electromagnetic absorption structures and may find potential applications in multi-functional planar or conformal structures.